1984
DOI: 10.1121/1.390778
|View full text |Cite
|
Sign up to set email alerts
|

A finite difference solution for the propagation of sound in near sonic flows

Abstract: SUMMARYAn explicit time/space finite difference procedure is used to model the propagation of sound in a quasi one-dimensional duct containing high Mach number subsonic flow. Nonlinear acoustic equations are derived by perturbing the time-dependent Euler equations about a steady, compressible mean flow. The governing difference relations are based on a fourth-order, two-step (predictor-corrector) MacCormack scheme. Difference equations for the source and termination boundary conditions are derived from the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This shows that (ELAST) models a boundary surface with specific acoustic impedance [1, p. 261] given by £ = z/(pc) = iu>/(ct + iuj (3). The magnitude of the reflection is smaller than 1 if and only if (3 > 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that (ELAST) models a boundary surface with specific acoustic impedance [1, p. 261] given by £ = z/(pc) = iu>/(ct + iuj (3). The magnitude of the reflection is smaller than 1 if and only if (3 > 0.…”
Section: Introductionmentioning
confidence: 99%
“…The need for boundary conditions formulated in the time domain is a well publicized need [2] that has been unresolved for years. Generally, only total reflection or absorption (being constant with frequency) have been formulated as boundary conditions in the time domain [3]. This includes the applications of Sommerfield's radiation condition in the free field.…”
Section: Introductionmentioning
confidence: 99%
“…However, a sequence of study reported by Hariharan and Lester [4,5] for one-dimensional problems and by Hariharan [6] for two-dimensional problems of nonlinear acoustic calculations shows that only two terms are needed to investigate the nonlinearity, even for the case of shock waves. A natural question one may ask is why not solve the nonlinear problem directly, as in the above references, including discontinuities in the solutions such as shock waves.…”
mentioning
confidence: 99%